PENGARUH KEPUASAN DAN KOMPENSASI PENGGUNA SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN - Estoy Putri Pertama; Endang Masitoh W.; Anita Wijayanti (Universitas Slamet Riyadi, 2021)
Knowing how significant the effect of satisfaction and compensation is on employee performance is the aim of this study. The questionnaire used is population and sample, namely all employees who work at the Surakarta City Hall employee office in the DPMPTSP section. The sampling technique used convenience sampling with a research sample of 61 respondents. The data analysis technique used in this study is multiple linear regression using the SPSS for windows program. The analytical tools in this study used validity and reliability tests, classic assumption tests (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test) while data analysis used multiple linear regression tests, t test, F test and coefficient of determination (R2). Based on the results of the t test analysis carried out, it shows that there is a positive effect of satisfaction and compensation on employee performance and simultaneously the variables of satisfaction and compensation have an effect on employee performance.